Coping strategies and risk of cardiovascular disease incidence and mortality: the Japan Public Health Center-based prospective Study - Svensson, Thomas; Inoue, Manami; Sawada, Norie; Yamagishi, Kazumasa; Charvat, Hadrien; Saito, Isao; Kokubo, Yoshihiro; Iso, Hiroyasu; Kawamura, Noriyuki; Shibuya, Kenji; Mimura, Masaru; Tsugane, Shoichiro (European heart journal, 2016)
Coping strategies may be significantly associated with health outcomes. This is the first study to investigate the association between baseline coping strategies and cardiovascular disease (CVD) incidence and mortality in a general population cohort. The Japan Public Health Center-based prospective Study asked questions on coping in its third follow-up survey (2000-04). Analyses on CVD incidence and mortality included 57 017 subjects aged 50-79 without a history of CVD and who provided complete answers on approach- and avoidance-oriented coping behaviours and strategies. Cox regression models, adjusted for confounders, were used to determine hazard ratios (HRs) according to coping style. Mean follow-up time was 7.9 years for incidence and 8.0 years for mortality.The premorbid use of an approach-oriented coping strategy was inversely associated with incidence of stroke (HR = 0.85; 95% CI, 0.73-1.00) and CVD mortality (HR = 0.74; 95% CI, 0.55-0.99). Stroke subtype analyses revealed an inverse association between the approach-oriented coping strategy and incidence of ischaemic stroke (HR = 0.79; 95% CI, 0.64-0.98) and a positive association between the combined coping strategy and incidence of intra-parenchymal haemorrhage (HR = 2.03; 95% CI, 1.01-4.10). Utilizing an avoidance coping strategy was associated with increased mortality from ischaemic heart disease (IHD) only in hypertensive individuals (HR = 3.46; 95% CI, 1.07-11.18). The coping behaviours fantasizing and positive reappraisal were associated with increased risk of CVD incidence (HR = 1.24; 95% CI, 1.03-1.50) and reduced risk of IHD mortality (HR = 0.63; 95% CI, 0.40-0.99), respectively. An approach-oriented coping strategy, i.e. proactively dealing with sources of stress, may be associated with significantly reduced stroke incidence and CVD mortality in a Japanese population-based cohort.